The Language of Genetics : an Introduction - Alexander, Denis (Denis Raven), 1945- (Templeton science and religion series., 2011)
The Language of Genetics: An Introduction is the seventh title published in the Templeton Science and Religion Series, in which scientists from a wide range of fields distill their experience and knowledge into brief tours of their respective specialties. In this volume, Dr. Denis R. Alexander offers readers a basic toolkit of information, explanations, and ideas that can help us grasp something of the fascination and the challenge of the language of genetics. Alexander surveys the big picture, covering such topics as the birth of the field; DNA: what it is, how it works, and how it was discovered; our genetic history; the role of genes in diseases, epigenetics, and genetic engineering. The book assumes the reader has little scientific background, least of all in genetics, and approaches these issues in a very accessible way, free of specialized or overly technical jargon. In the last chapter, Dr. Alexander explores some of the big questions raised by genetics: what are its implications for notions of human value and uniqueness? Is evolution consistent with religious belief? If we believe in a God of love, then how come the evolutionary process, utterly dependent upon the language of genetics, is so wasteful and involves so much pain and suffering? How far should we go in manipulating the human genome? Does genetics subvert the idea that life has some ultimate meaning and purpose? Genetics is a rapidly advancing field; it seems new discoveries make headlines every other week. The Language of Genetics is intended to give the general reader the knowledge he or she needs to assess and understand the next big story in genetics.